Pembuatan Sistem Informasi Akuntansi Pada Berjaya Sport - Vincent Tio Pratama; Ramdana, Mariska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2024)
Technology is moving in a more modern direction, certainly allowing users to enjoy greater convenience and efficiency in its use. Of course, in this era of a growing economy, MSME (Micro, Small and Medium Enterprises) are encouraged by the government to take advantage of this development by adopting information systems in their business, both for record keeping and as a reference for their business performance. Berjaya Sport is a business that provides sports equipment, especially in badminton, ranging from equipment such as rackets, shoes, clothing and other accessories, not to forget the professional string service are provided here. With friendly prices, so that the satisfaction of regular customers is able to make Berjaya Sports one of the options for badminton sports fans in Batam City. With the development of business turnover continues to grow, with manual recording will certainly be tiring and less effective, and if the inventory card is lost requires them to recalculate their entire inventory. So, from these problems, the author is encouraged to help to implement an accounting information system to Berjaya Sport. As a result, the recording of transactions and digital inventory and reports that can be used as a performance reference can be accessed directly in the system. The objective of this project is to make partners more effective and efficient in both entering and analyzing their business